Educational mobile augmented reality edupark game: does it improve students learning? - Pombo, Lúcia (2019)
Mobile devices are being intensively used by the Portuguese youth in their daily life, but not in school activities. Despite this gap, research shows that technology can promote student learning in non-high education contexts. This paper comprises a survey study where mobile learning is analyzed through the eyes of 244 students attending the 2nd or 3rd Cycles of Basic Education (CBE). The acknowledged advantages and difficulties of the use of mobile devices for learning, as well as the educational value and usability of a specific mobile learning strategy, using the EduPARK app and game, were analyzed. Results revealed that most students owned a mobile device and were able to use them to learn. They had a positive perspective regarding mobile learning and valued the advantages of being easy to find up-to-date information, motivating for learning and easy to carry along. Nevertheless, students acknowledged difficulties in the use of mobile devices to learn, such as requiring an internet connection, its slowness, not being allowed to use mobile devices in schools as they facilitate access to distractions. The EduPARK game achieved an average Educational Value Scale of 83.8 and an average System Usability Scale of 80.2, indicating its high educational value and usability for students. This paper presents empirical evidence regarding the effectiveness of the integration of mobile game-based AR approaches in 2nd and 3rd CBE to promote students learning. It also includes an example of excellent interdisciplinary educational materials that comprises a very useful tool for teachers and students to explore scientific knowledge by accessing appealing information on biological and historical references of a local urban park.